Simulating harvest strategy trade-offs for tuna fisheries in the Western and Central Pacific Ocean - Ciara Willis; Quentin Hanich; Colette C.C. Wabnitz; Susan Roxas; Nilmawati; Fayakun Satria; Lilis Sadiyah; Isidro Tanangonan; Megan Bailey (Marine Policy, 2026)

Putting Regional Fisheries Management Organisations' Climate Change House in Order - Kamal Azmi; Graham Pilling; Johann Bell; Yi‐Jay Chang; Adele Dutilloy; Timothy H. Frawley; Paul Hamer; John Hampton; Quentin Hanich; Tyla Hill‐Moana; Jhen Hsu; Glenn Hurry; et al. (Fish and Fisheries, 2025)
Climate change is expected to have significant impacts on the biology, abundance and distribution of transboundary fish stocks, not only among neighbouring countries within the jurisdictions of regional fisheries management organisations (RFMOs) but also between adjacent RFMOs. Using South Pacific albacore tuna ( Thunnus alalunga ) as a case study, we highlight how RFMOs need to understand the impacts of climate change on transboundary stocks under their purview with greater certainty. We identify four areas of research that should assist RFMOs to adapt their scientific processes—strengthened understanding of changes in the biology of target stocks; enhanced collection of data to support modelling; improved modelling of catch‐per‐unit of effort (CPUE) to better reflect climate change impacts on stock abundance for assessments; and ensuring that scientific advice is adaptive and robust to climate change, including through implementation of tested harvest strategies. Investments in these research areas should enable RFMOs to improve the science underpinning management measures designed to sustain transboundary stocks and increase fishery performance during climate change.

Policy pathways to reduce disproportionate burdens in tuna fisheries - Bianca Haas; Kamal Azmi; Hussain Sinan; Quentin Hanich (Fish and Fisheries, 2024)
The United Nations Fish Stocks Agreement requires states to recognise the special requirements of developing countries and to ensure that conservation and management measures do not place a disproportionate burden on developing countries. The aim of this article is to assess what policy arrangements are required to reduce the identified disproportionate burden. We developed a policy pathway that would allow members of tuna regional fisheries management organisations (tRFMOs) to strengthen their efforts to meet their duty to share conservation burdens more equitably. This pathway consists of policy options that were developed by using policy analysis, which is an innovative approach that provides actionable outcomes that can be used by tRFMO member states. Despite the global attention to reducing disproportionate conservation burdens, developing states are still suffering. The results of this article provide novel and timely policy options that have the potential to reduce the conservation burden carried by developing states.

The unintended consequences of exemptions in conservation and management measures for fisheries management - Bianca Haas; Kamal Azmi; Quentin Hanich (Ocean & Coastal Management, 2023)

Enhancing cooperative responses by regional fisheries management organisations to climate-driven redistribution of tropical Pacific tuna stocks - Camille Goodman; Ruth Davis; Kamal Azmi; Johann Bell; Grantly R. Galland; Eric Gilman; Bianca Haas; Quentin Hanich; Patrick Lehodey; Lara Manarangi-Trott; Simon Nicol; Pablo Obregon; et al. (Frontiers in Marine Science, 2022)
Climate change is predicted to alter the distributions of tropical tuna stocks in the Pacific Ocean. Recent modelling projects significant future shifts in tuna biomass from west to east, and from national jurisdictions to high seas areas. As the distributions of these stocks change, the relevant regional fisheries management organisations (RFMOs)—the Western and Central Pacific Fisheries Commission (WCPFC) and the Inter-American Tropical Tuna Commission (IATTC)—will need to develop an expanded framework for cooperation and collaboration to fulfil their conservation and management responsibilities under international law. The key elements of a possible expanded framework for cooperation can be developed, and fundamental areas for collaboration identified, by applying and adapting principles established in the United Nations Convention on the Law of the Sea, the United Nations Fish Stocks Agreement, and the constituent instruments of the RFMOs themselves. Our analysis reveals a wide range of important issues requiring cooperation, and three clear priorities. First, a formal mechanism for cooperation is needed to enable effective and efficient decision-making and action by the two RFMOs on key issues. Second, further cooperation is required in scientific research and modelling to better understand the biology and distributions of Pacific tuna stocks and how they will respond to climate change, and to inform stock assessments and harvest strategies. Third, the RFMOs must cooperate to define appropriate limits on fishing for each stock in a way that ensures they are compatible across the two organisations, taking into account their different members and management regimes.

Who Gets the Catch? How Conventional Catch Attribution Frameworks Undermine Equity in Transboundary Fisheries - Ruth A. Davis; Quentin Hanich; Bianca Haas; Andrés M. Cisneros-Montemayor; Kamal Azmi; Katherine L. Seto; Wilf Swartz; Pedro C. González-Espinosa; Mathieu Colléter; Timothy J. H. Adams (Frontiers in Marine Science, 2022)
The focus on flag States for the purpose of attributing fisheries catch is inconsistent with the assignment of sovereign rights to coastal States under international law and undermines equity in contemporary quota allocation negotiations. We propose modernizing reporting frameworks to include zone-based reporting of fish catches to more equitably present data, ensure consistency with the Law of the Sea, and better support the realization by developing coastal States of their development aspirations consistent with SDG 14, Life Below Water. States are already required to collect the data necessary to support this change, and many regional fisheries management authorities already do so. Reforms to data collection and reporting mechanisms should support zone-based catch attribution as a central feature of negotiations around access to future fishing opportunities on shared resources. Doing so will ensure that the sovereign rights of developing coastal States are properly accounted for and implemented.

Area‐based management of blue water fisheries: Current knowledge and research needs - Ray Hilborn; Vera N. Agostini; Milani Chaloupka; Serge M. Garcia; Leah R. Gerber; Eric Gilman; Quentin Hanich; Amber Himes‐Cornell; Alistair J. Hobday; David Itano; Michel J. Kaiser; Hilario Murua; et al. (Fish and Fisheries, 2022)
The pelagic fisheries beyond the continental shelves are currently managed with a range of tools largely based on regulating effort or target catch. These tools comprise both static and dynamic area‐based approaches to include gear limitations, closed areas and bycatch limits. There are increasing calls for additional area‐based interventions, particularly expansion of marine protected areas, with many now advocating closing 30% of the oceans to fishing. In this paper, we review the objectives, methods and successes of area‐based management of blue water fisheries across objectives related to food production and environmental, social and economic impacts. We also consider the methods used to evaluate the performance of area‐based regulations and provide a summary of the relative quality of evidence from alternative evaluation approaches. We found that few area‐based approaches have been rigorously evaluated, and that it is often difficult to obtain requisite observational data to define a counterfactual to infer any causal effect for such evaluation. Management agencies have been relatively successful at maintaining important commercial species at or near their target abundance, but success at meeting ecological or social goals is less clear. The high mobility of both target and bycatch species generally reduces the effectiveness of area‐based management, and shifting distributions due to climate change suggest that adaptive rather than static approaches will be preferred. We prioritize research and management actions that would make area‐based management more effective.

Common but differentiated rights and responsibilities in tuna fisheries management - Hussain Sinan; Megan Bailey; Quentin Hanich; Kamal Azmi (Fish and Fisheries, 2022)
The UN Law of the Sea Convention (LOSC) and one of the implementing agreements of the Convention—the UN Fish Stocks Agreement (UNFSA)—mandates all states to cooperate in the management of highly migratory and straddling fish stocks. In doing so, the UNFSA specifies that the special requirements of developing states need to be taken into account. To date, except in the Western and Central Pacific Fisheries Commission (WCPFC), there is no formal mechanism to identify these differential responsibilities in tuna regional fisheries management organizations (RFMOs). Although some conservation and management measures exempt small‐scale and artisanal fishing vessels, power imbalances within RFMOs tend to favour the interests of more developed and larger distant water fishing nations over those of small developing coastal states. To facilitate the implementation of differentiated responsibilities as mandated in UNFSA, in this study we develop a three‐step framework that could be applied in the case of new conservation and management measure proposals. The framework has also been tested based on two developing countries and compared with a developed state in the Indian Ocean Tuna Commission and the adopted resolutions in 2019. To facilitate better transparency and equitable decision‐making processes across RFMOs, this framework could be adapted based on member states' fisheries management objectives and target and non‐target species.

Resource allocation in transboundary tuna fisheries: A global analysis - Katherine Seto; Grantly R. Galland; Alice McDonald; Angela Abolhassani; Kamal Azmi; Hussain Sinan; Trent Timmiss; Megan Bailey; Quentin Hanich (Ambio, 2021)
Resource allocation is a fundamental and challenging component of common pool resource governance, particularly transboundary fisheries. We highlight the growing importance of allocation in fisheries governance, comparing approaches of the five tuna Regional Fisheries Management Organizations (tRFMOs). We find all tRFMOs except one have defined resources for allocation and outlined principles to guide allocation based on equity, citizenship, and legitimacy. However, all fall short of applying these principles in assigning fish resources. Most tRFMOs rely on historical catch or effort, while equity principles rarely determine dedicated rights. Further, the current system of annual negotiations reduces certainty, trust, and transparency, counteracting many benefits asserted by rights-based management proponents. We suggest one means of gaining traction may be to shift conversations from allocative rights toward weighting of principles already identified by most tRFMOs. Incorporating principles into resource allocation remains a major opportunity, with important implications for current and future access to fish.

Linking Capacity Development to GOOS Monitoring Networks to Achieve Sustained Ocean Observation - Nicholas J. Bax; Ward Appeltans; Russell Brainard; J. Emmett Duffy; Piers Dunstan; Quentin Hanich; Harriet Harden Davies; Jeremy Hills; Patricia Miloslavich; Frank Edgar Muller-Karger; Samantha Simmons; O. Aburto-Oropeza; et al. (Frontiers in Marine Science, 2018)